Intuitionistic Fuzzy n-Ary Subgroups: D.R. Prince Williams - Team, Support (Thai Journal of Mathematics, 2010)
In this paper, we introduce a notion of an intuitionistic fuzzy n-ary subgroup in an n-ary group (G, f) and have studied their related properties.